Exploring the Professional Identity Development of English Lecturers as Tech-Savvy Educators - Rizka Safriyani; Pratiwi Retnaningdyah; Ahmad Munir; Mohammad Romadhoni (IJORER : International Journal of Recent Educational Research, 2024)
Objective: The professional identity of lecturers evolved because of the complexity of professional activities and policies. This study aims to discover how English Literature Lecturers cultivate their professional identity as Techno Savvy. Method: This qualitative case study is an endeavor to address how English literature lecturers'' cultivate their professional identity as tech-savvy lecturers. Four English lecturers voluntarily participated in this study. Semi-structured interviews and observations were done to learn how English Literature Lecturers cultivate their identity. Thematic analysis was used, and methodological triangulation was chosen to ensure objectivity. Results: The result indicates that English LLecturers'' cultivated their identity as a technology-savvy lecturer through their learning media and learning activities used in the classroom. Joining technology professional development sessions and the Technology Enhanced Language Learning Association becomes the external motivation that socially constructs their identity. Novelty: The study found that the type of professional activities, university policy, and social identification influenced Professional Identity Development.